2005
DOI: 10.1260/0958305053516172
|View full text |Cite
|
Sign up to set email alerts
|

Utility Green Pricing Programs: A Statistical Analysis of Program Effectiveness

Abstract: Utility green pricing programs represent one way in which consumers can voluntarily support the development of renewable energy. The design features and effectiveness of these programs varies considerably. Based on a survey of utility program managers in the United States, this article provides insight into which program features might help maximize both customer participation in green pricing programs and the amount of renewable energy purchased by customers in those programs. We find that program length has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Customers respond well to premium pricing tactics in several regions. The quality of items with green premium pricing has also been proven to be greater [72]. Furthermore, research have shown that the majority of consumers are prepared to pay a premium for already available ecologically friendly items [73].…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Customers respond well to premium pricing tactics in several regions. The quality of items with green premium pricing has also been proven to be greater [72]. Furthermore, research have shown that the majority of consumers are prepared to pay a premium for already available ecologically friendly items [73].…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…10. Wiser et al (2005), Mewton & Cacho (2011), Conte &Jacobsen (2016), andDagher et al (2017) use actual plan participation data to estimate the impact of price premiums on green participation behavior (among other factors of interest) and find that price premium negatively impacts green participation, and demand is relatively price inelastic.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…This allows consumers to purchase electricity at a reduced cost [9]. By redistributing excess prosumer electricity, prosumers are optimizing their investment by minimizing curtailment while also improving utility resource allocation [10,11].…”
Section: Introductionmentioning
confidence: 99%